Bacteraemia Caused by Probiotic Strains of Lacticaseibacillus rhamnosus—Case Studies Highlighting the Need for Careful Thought before Using Microbes for Health Benefits - Agnieszka Mikucka; Aleksander Deptuła; Tomasz Bogiel; Agnieszka Chmielarczyk; Elżbieta Nurczyńska; Eugenia Gospodarek-Komkowska (Pathogens, 2022)
Lactic acid bacteria belonging to Lactobacillus spp. and Lacticaseibacillus spp. are a natural part of fermented milk and other food products, probiotic supplements and human microbiota. They mainly belong to mucosal microflora, especially oral, vaginal and intestinal. Lacticaseibacillus spp. strains included in probiotics are generally characterised as safe microorganisms, and the species are concerned bacteria with very low pathogenic potential. However, infections caused by Lactobacillus spp. and Lacticaseibacillus spp., including bacteraemia and endocarditis, occur occasionally. The aim of the study was to present two cases of bacteraemia due to Lacticaseibacillus rhamnosus associated with the use of a probiotic product. It afflicted patients in intensive care units. The investigation was preliminarily based on clinical and microbiological recognition of the cases. The initial observation was laboratory confirmed with the application of pulsed-field gel electrophoresis (PFGE) results. Identical PFGE patterns were obtained for the evaluated strains and the strains derived from a commercially available probiotic that was administered to those patients. The increasing number of studies describing opportunistic infections due to probiotic strains of Lacticaseibacillus spp. should result in verifying the safety of probiotic formulations used in immunocompromised patients and forming detailed guidelines for the use of probiotics among patients from several risk groups.